2013
DOI: 10.1111/jvs.12146
|View full text |Cite
|
Sign up to set email alerts
|

Habitat invasion research: where vegetation science and invasion ecology meet

Abstract: In the last decade, habitat-oriented studies of plant invasions, performed at broad scales and using large data sets of vegetation plots, have focused on quantifying the representation of alien species in vegetation or habitat types, identifying factors underlying invasions, and exploring the pools of species available for invasion into particular habitats. In this essay we summarize what we have learned, discuss constraints associated with this kind of data and outline promising research topics to which a mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 55 publications
2
21
0
Order By: Relevance
“…Recent studies have demonstrated that habitat characteristics play an important role in determining the patterns of invasions by alien plant species (Catford et al, 2012;Py sek & Chytr y, 2014). However, habitats in the invaded ranges have been the main focus of research so far (Stohlgren et al, 1999(Stohlgren et al, , 2006Chytr y et al, 2005Chytr y et al, , 2008bVil a et al, 2007;Affre et al, 2010;Py sek et al, 2010aPy sek et al, , 2012, including studies of their invasibility versus actual level of invasion (Chytr y et al, 2008a,b).…”
Section: Introductionmentioning
confidence: 96%
“…Recent studies have demonstrated that habitat characteristics play an important role in determining the patterns of invasions by alien plant species (Catford et al, 2012;Py sek & Chytr y, 2014). However, habitats in the invaded ranges have been the main focus of research so far (Stohlgren et al, 1999(Stohlgren et al, , 2006Chytr y et al, 2005Chytr y et al, , 2008bVil a et al, 2007;Affre et al, 2010;Py sek et al, 2010aPy sek et al, , 2012, including studies of their invasibility versus actual level of invasion (Chytr y et al, 2008a,b).…”
Section: Introductionmentioning
confidence: 96%
“…In ecology, community assembly constitutes a relevant issue from the theoretical and applied points of view (Young et al, 2001;Hillebrand and Matthiessen, 2009;HilleRisLambers et al, 2012;Py sek and Chytrý, 2014). Most studies on species co-occurrence have focussed upon the importance of different ecological factors acting on the species present in a given region such as dispersal, abiotic filters and biotic interactions (Chase, 2003;Diamond, 1975;G€ otzenberger et al, 2011;Casado et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, scientists have used vegetation survey data and plant species lists to compare the levels of alien plant invasion across habitats in Europe, for example in Catalonia (Vilà, Pino, & Font, 2007), Basque Country (Campos, Biurrun, García-Mijangos, Loidi, & Herrera, 2013), Czech Republic (Chytrý, Pyšek, Tichý, Knollová, & Danihelka, 2005) and Slovakia (Medvecká, Jarolímek, Senko, & Svitok, 2014) (see also review by Pyšek & Chytrý, 2014). While not a surrogate of invasibility per se (see Chytrý, Jarošik et al, 2008;Lonsdale, 1999;Richardson & Pyšek, 2006), the levels of alien plant invasion can point to mechanisms underlying plant invasions, particularly if levels are similar in corresponding habitats across regions.…”
Section: Introductionmentioning
confidence: 99%